Post-activation performance enhancement in strength and power sports - A narrative review - Olsen, O. R.; Bojsen-Møller, J.; Aagaard, P. (Scandinavian Journal of Medicine & Science in Sports, 2025)
The aim of this narrative review was to examine the effects and mechanisms of Post-Activation Performance Enhancement (PAPE) on sports and exercise performance, and to provide practical recommendations on its application. PAPE denotes the phenomenon of acute enhancements in contractile performance (e.g., enhanced strength, rate of force development or power) following a given conditioning activity (CA). PAPE can be utilized in a wide range of athletic disciplines, is manifested for both upper and lower body muscle exertions and may be exploited to boost performance during training and competition. Several physiological mechanisms have been proposed to underlie PAPE, including phosphorylation of contractile proteins and increased excitability of motor pathways in the nervous system. Other proposed mechanisms include transient alterations in muscle architecture, increased limb stiffness, and increases in skeletal muscle temperature. Repeated muscle contractions generate both acute fatigue and contractile potentiation, the net balance of which determines if physical performance subsequently is enhanced or attenuated. Decreases in performance are typically observed initially following CA, after which supercompensatory effects emerge typically at 4-9 min post CA. For conventional resistance exercise, CA protocols utilizing loading intensities >= 60% 1RM appear to induce the greatest magnitude of PAPE. Notably, a range of specific CA protocols can elicit PAPE, including conventional resistance training exercises, plyometric drills as well as blood flow restriction. In conclusion, when CA protocols are properly designed and executed, PAPE appears to enhance physical performance within both training and competition, and may be utilized during resistance training, jumping, and sprinting.